White‐Emitting Conjugated Polymer/Inorganic Hybrid Spheres: Phenylethynyl and 2, 6‐Bis(pyrazolyl)pyridine Copolymer Coordinated to Eu(tta)3. (24th June 2013) - Narayana, Yemineni S. L. V.; Basak, Supratim; Baumgarten, Martin; Müllen, Klaus; Chandrasekar, Rajadurai
Abstract The synthesis of two cyan color (blue and green emission) displaying high molecular weight 2, 6‐bis(pyrazolyl)pyridine‐co‐octylated phenylethynyl conjugated polymers (CPs) is presented. The conjugated polymers are solution‐processed to prepare spin coated thin films and self‐assembled nano/microscale spheres, exhibiting cyan color under UV. Additionally, the metal coordinating ability of the 2, 6‐bis(pyrazolyl)pyridine available on the surface of the CP films and spheres is exploited to prepare red emitting Eu(III) metal ion containing conjugated polymer (MCCP) layer. The fabricated hybrid (CP/MCCP) films and spheres exhibit bright white‐light under UV exposure. The Commission Internationale de l'Eclairage (CIE) coordinates are found to be (x = 0.33, y = 0.37) for hybrid films and (x = 0.30, y = 0.35) for hybrid spheres. These values are almost close to the designated CIE coordinates for ideal white‐light color (x = 0.33, y = 0.33). This easy and efficient fabrication technique to generate white‐color displaying films and nano/microspheres signify an important method in bottom‐up nanotechnology of conjugated polymer based hybrid solid state assemblies.